Capacity Building for Landslides Risk Reduction in Tamil Nadu State: A Critical Study on Plans and Practices: Exploring Strategies for Landslides Risk Reduction (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A landslide is considered as one of the most common and natural disasters which is basically caused by the heavy precipitation, floods, earthquakes and erosion and by anthropogenic activities. Several causalities or unwanted reports are reported after large floods, rainstorms and earthquake are mainly caused by the landslides generated by these events. We highly required global support and assistance to decrease the losses in the nations where there is high risk of landslides. The current study investigate about the threats and warning related to landslides with respect to influence of change in climate and the process and methods used for landslides risk management and reduction.